An Integrative Approach to New Chinese Ink Painting through Digital Art - Jia Xi, Liew (Universiti Malaysia Sarawak, 2025)
This study explores the integration of traditional Chinese Ink Painting with digital art, addressing the tension between preserving cultural heritage and embracing technological innovation. By anchoring the research in Xie He’s Six Principles (liufa)—a foundational theory of classical Chinese aesthetics—the study investigates how digital tools can reinterpret traditional ink techniques while retaining their philosophical and aesthetic essence. A qualitative approach combining visual analysis of historical and contemporary artworks, content analysis of artists’ statements, and practice-led research was employed. The classical Chinese Ink Paintings and digital ink artworks were analysed to identify continuities and innovations in Chinese ink painting’s theory. The study also documents the creation of Borders Unbroken: The Soul of Salako Dayak, a digital artwork integrating Salako Dayak cultural background with ink aesthetics, exhibited at UNIMAS’s FACA Gallery. Findings reveal that digital technologies can preserve traditional aesthetics while enabling participatory and immersive experiences, fostering cross-cultural dialogue. However, challenges persist in balancing technological experimentation with cultural authenticity.